The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1726-46342011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias clínicas y polisomnográficas entre obesos y no obesos con síndrome de apneas-hipopneas del sueño

Abstract: Objetivos. Describir las diferencias clínicas y polisomnográficas en pacientes obesos y no obesos con diagnóstico del síndrome de apneas-hipopneas del sueño (SAHS). Materiales y métodos. A los pacientes incluidos se les realizó un examen físico, se aplicó la escala de somnolencia de Epworth (ESE) y además se les realizó una polisomnografía. Se consideró obeso si el índice de masa corporal (IMC) era mayor o igual a 30 kg/m 2 . Resultados. Se analizaron 408 pacientes con SAHS, de estos, 119 (47 %) fueron obesos.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The strongest association between anthropometric measurements and sleep disorders was observed between WC and OSA, which makes sense given the visceral fat deposition which causes instability and collapsibility of the upper airway [6,32,33]. However, unlike in previous studies, NC did not correlate with the presence of OSA [7,32,[34][35][36][37][38]; this could be explained by differences in fat deposition patterns across populations, and heterogeneous measurements between reports [33]. In our study, BMI showed a stronger correlation with WC than with NC (r = 0.75 and 0.65, respectively), and WC was poorly correlated with NC (r = 0.69 in men and r = 0.63 in women).…”
Section: Discussionmentioning
confidence: 89%
“…The strongest association between anthropometric measurements and sleep disorders was observed between WC and OSA, which makes sense given the visceral fat deposition which causes instability and collapsibility of the upper airway [6,32,33]. However, unlike in previous studies, NC did not correlate with the presence of OSA [7,32,[34][35][36][37][38]; this could be explained by differences in fat deposition patterns across populations, and heterogeneous measurements between reports [33]. In our study, BMI showed a stronger correlation with WC than with NC (r = 0.75 and 0.65, respectively), and WC was poorly correlated with NC (r = 0.69 in men and r = 0.63 in women).…”
Section: Discussionmentioning
confidence: 89%
“…Preliminary studies with different objectives have been published with other subgroups of this population [2325]. …”
Section: Methodsmentioning
confidence: 99%
“…De acuerdo a la Organización Mundial de la Salud, el síndrome de apnea e hipopnea obstructiva del sueño (SAHOS) es, desde inicios del año 2000, una pandemia silenciosa que presenta una incidencia aproximada de uno por cada veinte adultos, por lo que es considerado un problema de salud pública. La obesidad es un importante factor de riesgo para el desarrollo de SAHOS, se calcula que dos de cada tres pacientes con SAHOS tienen obesidad; además, la frecuencia de SAHOS puede llegar al 50% en aquellas personas con obesidad mórbida, quienes incluso pueden desarrollar formas más severas de la enfermedad [1,2] . La frecuencia de SAHOS en pacientes sometidos a cirugía, especialmente aquellos con cirugía bariátrica, es mayor que en la población general, con valores que oscilan entre el 25% al 70% [3] ; situación que se ha asociado con un mayor riesgo de complicaciones perioperatorias como intubación difícil, delirio posoperatorio, arritmias sostenidas, hipertensión arterial, ingresos a la Unidad de Cuidados Intensivos y una estancia hospitalaria prolongada [4][5][6] .…”
Section: Introductionunclassified